The Conversatorio Universitario (University Discussion) of 1919 and its historical significance - García Higueras, Gabriel (2019)
A few years before the commemoration of the centennial of the national independence, a group of students from the San Marcos University opened a conference cycle which would be known as the Conversatorio Universitario (University Discussion). This academic activity, endorsed by Raul Porras Barrenechea proposed, from a historical perspective, new approaches to the Emancipation era during the 1800-1825 period. Conversatorio Universitario activities began in June 1919. Its participants were young students, who presented their progress in research being developed. In their research the independence of Peru was approached from different points of view. Subsequently, the commentators –members of the named «Centennial Generation»– would accomplish a distinguished endeavor in the country’s intellectual life; among there were Raul Porras, Jorge Guillermo Leguia, Luis Alberto Sanchez and Manuel G. Abastos. During the enactment of the Conversatorio Universitario two events took place which would leave a profound mark in Peruvian life: the University Reform and the rise to power of Augusto B. Leguia.